Noble Qur’an defends the last of the prophets, (peace and blessings be upon him) - Zahedy, Abdullah (Journal of Islamic Sciences, 2020)
I wrote in this article the accusations that the polytheists accused the Messenger of God, as it came in the noble Qur’an, mentioning humanity, hatred and abandonment, madness, magic, priesthood, poetry....... Then I showed the error of the polytheists and their distance from right in these accusations in the evidence from the Holy Qur’an and reason and the sayings of the largest participants. Thanks to him witnessed the enemy until the grace of the enemies It relied on clarifying the charge, its statement and how to respond to it, and this is the greatest method in responding to the charges of the participants, because the one who takes charge of the defense and the response is the right to bless. (Say anything greater than the testimony. Say God is a witness between me and you, and I am inspired).